On the upper and lower surfaces for the m-dimensional homogeneous gaussian processes with independent increments - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Н. Калинаускайте. О верхних и нижних поверхностях для m-мерных однородных гауссовских процессов с независимыми приращениямиN. Kalinauskaitė. Viršutiniai ir apatiniai paviršiai m-mačiams homogeniniams Gauso procesams